Understanding punishment in Islamic Law from the educational perspective - Abd Rashid, Adnan (IIUM Press, International Islamic University Malaysia, 2015)
The key feature of Din-al-Islam is to guide people and preserve justice for every individual in society. The Islamic educational process is considered crucial to promote husnul khuluq (good character) and condemn sinful deeds. Apart from this, the Sharicah (Islamic law) seeks to create harmony between members of society. The punishment which is a component of the Sharicah (Islamic law) is also intended to maintain harmony in a society by means of deterring and reforming the offender. Nevertheless, the process of tarbiyyah Islamiyyah (Islamic education) is given the priority compared to the punishment, where punishment is considered as a last resort.This book shows the long process of tarbiyyah Islamiyyah (Islamic education) which is considered crucial in an individual’s life in order to develop and inculcate husnul khuluq (good character). If men are nurtured through this process and able to embed it in their life, punishment seems to be unnecessary. If one persists in committing crime, this book explains that punishment in Islam may play the role of discouraging, controlling and precluding the transgression and reforming the criminal.